1991
DOI: 10.1126/science.253.5021.774
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Extreme Upwelling Filaments in the Southeast Atlantic Ocean

Abstract: Cold oceanic water upwells along the western coastline of most major continents. The thermal front that demarcates the farthest seaward extent of this upwelled water is sometimes characterized by extensive whisps or cross-frontal filaments. These may play an important role in the functioning of the upwelling ecosystem as a whole. Satellite observations on filaments of the Benguela upwelling system show filaments that exceed 1000 kilometers in length. Two mechanisms that may produce the exceptional length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Bang and Andrews (1974) report a strongly baroclinic frontal zone near the shelfbreak that contain a strong equatorward jet with maximum velocity of 1.2 m/s and suggest an association with the local wind forcing. Lutjeharms et al (1991) observed a long 770 km filament that extended from the shelf in association with an Agulhas eddy near the Luderitz upwelling cell. Filaments are known to form in association with the elongation of an Agulhas ring and indicate tracer leakage (de Steur et al, 2004;Whittle et al, 2008).…”
Section: S Baker-yeboah Et Al: Transformation Of An Agulhas Eddy Nementioning
confidence: 99%
“…Bang and Andrews (1974) report a strongly baroclinic frontal zone near the shelfbreak that contain a strong equatorward jet with maximum velocity of 1.2 m/s and suggest an association with the local wind forcing. Lutjeharms et al (1991) observed a long 770 km filament that extended from the shelf in association with an Agulhas eddy near the Luderitz upwelling cell. Filaments are known to form in association with the elongation of an Agulhas ring and indicate tracer leakage (de Steur et al, 2004;Whittle et al, 2008).…”
Section: S Baker-yeboah Et Al: Transformation Of An Agulhas Eddy Nementioning
confidence: 99%
“…They may then encircle rings. In extreme cases, especially when there is a strong berg wind -an offshore movement of air from the higher continental escarpment -such interaction may result in upwelling filaments being drawn up to 1000 km offshore (Lutjeharms et al, 1991).…”
Section: Agulhas Ringsmentioning
confidence: 99%
“…For example, warm Agulhas rings entrain cold water from the Benguela upwelling system on their flanks and advect upwelled water far offshore as long filaments (Lutjeharms et al 1991). Likewise, warm core rings shed from the Gulf Stream and advected into the northern recirculation gyre often entrain shelf water, slope water, and/or Gulf Stream water on their fringes, creating important onshore and offshore fluxes of very diverse water masses-and their associated heat, freshwater and biogeochemical contents (Nof 1988, Ryan et al 2001).…”
Section: Discussionmentioning
confidence: 99%